DBS Assay with LC-MS/MS for the Determination of Idelalisib, A Selective PI3K-δ Inhibitor in Mice Blood and Its Application to a Pharmacokinetic Study - Tripathy, Harsha K.; Manju, Nair S.V.; Dittakavi, Sreekanth; Zakkula, Ashok; Mullangi, Ramesh (Drug Research, 2020)
Idelalisib is a selective and second-generation PI3K-δ inhibitor, approved for the treatment of non-Hodgkin lymphoma and chronic lymphocytic leukemia. In this paper, we present a fully validated dried blood spot (DBS) method for the quantitation of idelalisib from mice blood using an LC-MS/MS, which was operated under multiple reaction monitoring mode. To the punched DBS discs, acidified methanol enriched with internal standard (IS; larotrectinib) was added and extracted using tert-butyl methyl ether as an extraction solvent with sonication. Chromatographic separation of idelalisib and the IS was achieved on an Atlantis dC18 column using a mixture of 10 mM ammonium formate:acetonitrile (25:75, v/v). The flow-rate and injection volume were 0.80 mL/min and 2.0 µL, respectively. Idelalisib and the IS were eluted at ~0.98 and 0.93 min, respectively and the total run time was 2.00 min. Idelalisib and the IS were analyzed using positive ion scan mode and parent-daughter mass to charge ion (m/z) transition of 416.1→176.1 and 429.1→342.1, respectively was used for the quantitation. The calibration range was 1.01−4 797 ng/mL. No matrix effect and carry over were observed. Haematocrit did not influence DBS idelalisib concentrations. All the validation parameters met the acceptance criteria. The applicability of the validated method was shown in a mice pharmacokinetic study.
Keywords: anticancer drugs; pharmacokinetics; drug research